GAMBARAN MINAT MAHASISWA S1 KEPERAWATAN SEMESTER VIII MELANJUTKAN KE PROGRAM PROFESI NERS DI UNIVERSITAS MUHAMMADIYAH MAGELANG - Hidayah, Nurul; Masithoh, Robiul Fitri (Journal Of Holistic Nursing Science, 2017)
The quality of the generated students still needs to receive careful attention from various relatedelements, although there have been various educational improvements. The undergraduateeducation system of health is developed as a college-based professional education. Nursingundergraduate education produces various types of nursing personnel, whether the personnel inperforming services, personnel in the field of education, as well as personnel in the field ofresearch. One of the programs to develop professional care education is to follow professionalprogram ners. One of the programs offered by the University is by conducting Ners professionprogram, but in fact not all students are interested to proceed to the program. This study aimsto describe the interest of nursing undergraduate students Muhammadiyah University ofMagelang to continue the professional program ners. This study uses descriptive research thatdescribes the interest of students to follow the professional education program ners. The sampleused 24 undergraduate students of Nursing Faculty of Health Science Semester VIIIMuhammadiyah University of Magelang with purposive sampling technique. The instrumentused is the interest questionnaire to follow the Ners profession program. Data analysistechniques using univariat and descriptive.